2020
DOI: 10.1111/jfbc.13202
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extraction methods on the physicochemical, structural, functional, and antioxidant properties of the dietary fiber concentrates from male date palm flowers

Abstract: The current study evaluates the effect of both aqueous and alkaline extraction methods on the physicochemical, structural, functional, and antioxidant properties of dietary fibers (DF) from male date palm flowers (MDPF). The DF extracted by the alkali treatment (ADF) display a higher DF content as well as lower protein and lipid content than the DF resulting from watery extraction (WDF). The scanning electron microscopy, the Fourier‐transform infrared spectroscopy, and the X‐ray diffraction show that the alkal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Studies have indicated that these types of fibers found in diets offer several health advantages, such as enhancing the digestive system and minimizing the probability of developing long-term illnesses [109,110]. Several studies have investigated the extraction of dietary fibers from date processing waste using different methods, including enzymatic hydrolysis, acid and alkali treatments, and microwave-assisted extraction [78,111]. The extracted dietary fibers can be used as functional ingredients in the food industry, such as in the production of high-fiber bread, pasta, and snacks, as well as in the development of dietary supplements [112].…”
Section: Dietary Fibermentioning
confidence: 99%
“…Studies have indicated that these types of fibers found in diets offer several health advantages, such as enhancing the digestive system and minimizing the probability of developing long-term illnesses [109,110]. Several studies have investigated the extraction of dietary fibers from date processing waste using different methods, including enzymatic hydrolysis, acid and alkali treatments, and microwave-assisted extraction [78,111]. The extracted dietary fibers can be used as functional ingredients in the food industry, such as in the production of high-fiber bread, pasta, and snacks, as well as in the development of dietary supplements [112].…”
Section: Dietary Fibermentioning
confidence: 99%
“…DF can selectively promote metabolism and the proliferation of beneficial bacteria to produce energy and nutrients for the body (Williams et al, 2017). At present, methods for extraction of DF include mainly crude separation, chemical methods, membrane separation, enzymatic methods, enzymatic chemical combination methods, and fermentation methods (Yan et al, 2019;He YY et al, 2020;Karra et al, 2020). Miklavčič Višnjevec et al (2019) performed a modified enzymaticgravimetric method to determine the total, soluble, and insoluble fiber contents of jujube sample Zj2.…”
Section: Dietary Fibermentioning
confidence: 99%
“…Yuzu contains high levels of bioactive compounds, such as flavonoids, phenolic compounds, organic acids, and minerals that contribute to its biological activities, including antioxidant, antidiabetic, anti-inflammatory, neuroprotective, anticarcinogenic, and antihypertensive activities ( Kim et al, 2013 ; Lee et al, 2022 , Nam et al, 2021 ). Moreover, yuzu peel is rich in dietary fiber, primarily composed of cellulose, polysaccharides, lignin, and proteins that give their superior physicochemical properties, enhance their biodegradable properties, and contribute to human health benefits as dietetic ingredients ( Lv, Liu, Zhang, & Wang, 2017 ; Karra et al, 2020 , Nam et al, 2021 ). Therefore, yuzu has been used to produce various food products, such as fruits, sugar-pickled yuzu tea, aroma and flavor additives, and natural ingredients in biodegradable polymers and packaging materials ( Nam, et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%